Developing Talent for Organizational Results : Training Tools From the Best in the Field - Editor Biech, Elaine (San Francisco Pfeiffer, 2012)
While a single training company is often the provider for a client specific solutions, the combination of innovative approaches uncovered through the exchange of the collective experience of many providers/training suppliers creates a powerful arsenal of tools. These tools make a difference in the success of corporate enterprise-wide performance. ISA (The Association of Learning Providers) is the trusted network that brings suppliers together to share and debate the art and science of innovative learning and performance for work-related, enterprise-wide people performance on the job. This volume brings together ISA members to tell their story of what really works through a variety of activities, instruments, and articles"
Include Index
Keywords: Organizational change -- Employees--Training of -- Personnel management